Analysis of Automated Testing Frameworks for Web Applications based on Performance and Usability - Shidqi Adiatma; Ana Kurniawati (SISTEMASI, 2026)
Advances in information technology in recent years have accelerated digital transformation across various business sectors. This development is reflected in the increasing use of web-based applications that demand responsive, stable, and reliable system performance. However, software testing processes are still often performed manually, making them less efficient due to the significant time and resources required, as well as the potential for human error, particularly when applications undergo continuous feature updates. Therefore, a more effective testing approach through automation testing is required. This study aims to analyze and compare several automation testing frameworks to determine the most suitable framework for testing web applications. The testing scenarios were designed using a Domain Specific Language (DSL) approach based on Cucumber Gherkin syntax to ensure better readability and structured test cases. The evaluation was conducted based on two main aspects: Automated Testing Performance and Tools Usability. The performance aspect included time complexity, covered test cases, execution start time, and element inspection. Meanwhile, the usability aspect covered platform compatibility, supported browsers, scripting languages, and parallel execution capabilities. The case study was conducted on the web-based logistics application muatmuat.com, focusing on the register, login, and password reset features. The data were analyzed using the Multiple Attribute Decision Making (MADM) method with the Distance to the Ideal Alternative (DIA) approach. The results indicate that Selenium WebDriver achieved the lowest Ri value of 0.25799, followed by Cypress (0.31747), and both Playwright and WebdriverIO (0.33426), making Selenium WebDriver the most optimal framework among the evaluated alternatives.